Dynamic coordination control for hydraulic hub-motor auxiliary system based on NMPC algorithm. (15th March 2022) - Zeng, X.H.; Zhang, X.M.; Yang, D.P.; Song, D.F.; Qian, Q.F.; Wu, Q.T.
Highlights: A dynamic coordination control algorithm based on NMPC for HHMAS is proposed. A multi - mode pump displacement control algorithm is designed. The nonlinear controller of pump displacement actuator is designed based on Lyapunov stability principle. The controller performance is evaluated and compared with traditional PID and feedforward controllers. The results show the superiorities of the proposed dynamic coordination controller. Abstract: To solve the control problems caused by the driving force coordination and the essential nonlinearity of the hydraulic system in the working process of the Hydraulic Hub-Motor Auxiliary System (HHMAS), the study presents a dynamic coordination control algorithm based on Nonlinear-integrated Model Predictive Control (NMPC). Firstly, to achieve the target displacement control of the pump, the study designs a multi-mode pump displacement optimization algorithm; Secondly, a driving force coordination control strategy based on MPC is designed; Then, the nonlinear controller of the pump displacement actuator is designed based on the Lyapunov stability principle to realize the tracking control of the desired displacement. Finally, the simulation and HIL results show that the control error of NMPC controller is minimal, and the error control performance is improved by 93.78% and 74.3% respectively compared with steady-state feedforward and PID control, which greatly improves the dynamic control performance of the HHMAS.